2001
DOI: 10.1016/s0006-3495(01)75900-0
|View full text |Cite
|
Sign up to set email alerts
|

The Length Dependence of Translational Diffusion, Free Solution Electrophoretic Mobility, and Electrophoretic Tether Force of Rigid Rod-Like Model Duplex DNA

Abstract: In this work, boundary element modeling is used to study the transport of highly charged rod-like model polyions of various length under a variety of different aqueous salt conditions. Transport properties considered include free solution electrophoretic mobility, translational diffusion, and the components of the "tether force" tensor. The model parameters are chosen to coincide with transport measurements of duplex DNA carried out under six different salt/temperature conditions. The focus of the analysis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…A rigorous continuum hydrodynamic-electrodynamic model describing μ found that the effective charge per base pair decreases with increasing dsDNA length (Allison et al, 2001), indicating that significantly fewer counterions were accumulated per DNA charge for short DNA oligomers than for polymeric DNA. Treating DNA as straight hemispherically capped cylinders predicted electrophoretic mobilities for DNA 60 bp within < 9% of experimental values but overestimated μ for larger fragments (Fig.…”
Section: Oligoelectrolyte Capillary Electrophoresismentioning
confidence: 99%
“…A rigorous continuum hydrodynamic-electrodynamic model describing μ found that the effective charge per base pair decreases with increasing dsDNA length (Allison et al, 2001), indicating that significantly fewer counterions were accumulated per DNA charge for short DNA oligomers than for polymeric DNA. Treating DNA as straight hemispherically capped cylinders predicted electrophoretic mobilities for DNA 60 bp within < 9% of experimental values but overestimated μ for larger fragments (Fig.…”
Section: Oligoelectrolyte Capillary Electrophoresismentioning
confidence: 99%
“…3 (a body force) is assumed (see Remark 2.1) and the proof of the existence theorem as Theorem 3.1 is based on the solution of an approximated system (obtained by regularization techniques). The existence of the approximated solutions is obtained by the Schauder fi xedpoint theorem (see [5]), via a solution of an appropriate inhomogeneous (linear) Stokes equation.…”
Section: The Notion Of Weak Solutionmentioning
confidence: 99%
“…This phenomena is known as electrophoresis and is important in many technical applications (a vast literature is available: see for example [29], [24], [27], [2], [1], [3], [13], [30], [14]). We are considering a particle (a charged polymer, for example) immersed in an ionized solution (a viscous incompressible fluid).…”
Section: Introductionmentioning
confidence: 99%
“…Without much additional difficulty, this can be generalized to an "effective ellipsoid" approach [20] and applied to globular proteins [34,35]. In order to deal in a more realistic way with the irregular topography and charge distribution of a peptide or protein at the atomic or at least primary structure level, boundary element (BE) [34,36] and "bead model" [37 -39] approaches are available. The latter "bead model" approach is particularly useful when multiple conformations need to be sampled as is the case of particular peptides under a variety of solvent -buffer-pH conditions.…”
Section: Introductionmentioning
confidence: 99%